2018
DOI: 10.1093/pcp/pcy183
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Lithospermum erythrorhizon Reveals Regulation of a Variety of Metabolic Enzymes Leading to Comprehensive Understanding of the Shikonin Biosynthetic Pathway

Abstract: Plants produce a large variety of specialized (secondary) metabolites having a wide range of hydrophobicity. Shikonin, a red naphthoquinone pigment, is a highly hydrophobic metabolite produced in the roots of Lithospermum erythrorhizon, a medicinal plant in the family Boraginaceae. The shikonin molecule is formed by the coupling of p-hydroxybenzoic acid and geranyl diphosphate, catalyzed by a membrane-bound geranyltransferase LePGT at the endoplasmic reticulum, followed by cyclization of the geranyl chain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 42 publications
0
28
0
1
Order By: Relevance
“…10% of shikonin is produced as ester derivatives, which are secreted by cells, and plant masses can be easily enlarged in liquid suspension cultures 6 . Our multiple omics study identified 10 genes as being strongly involved in shikonin biosynthesis and 16 as being strongly involved in shikonin secretion 9 . The VIGS methodology described in this study will likely be utilized for functional analysis of these genes to determine the entire shikonin biosynthetic pathway and to understand mechanisms underlying its secretion.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…10% of shikonin is produced as ester derivatives, which are secreted by cells, and plant masses can be easily enlarged in liquid suspension cultures 6 . Our multiple omics study identified 10 genes as being strongly involved in shikonin biosynthesis and 16 as being strongly involved in shikonin secretion 9 . The VIGS methodology described in this study will likely be utilized for functional analysis of these genes to determine the entire shikonin biosynthetic pathway and to understand mechanisms underlying its secretion.…”
Section: Discussionmentioning
confidence: 91%
“…Shikonin is a meroterpene synthesized via two independent biosynthetic pathways, a common phenylpropanoid pathway and an isopreniod pathway 5 . Although several enzymes and genes involved in the initial steps of shikonin biosynthesis have been identified to date [6][7][8][9][10] , genes and proteins involved in later steps have not yet been identified, especially those involved in the crucial steps required to form the naphthalene ring.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Current efforts have extended to include synthetic chemistry for producing shikonin, alkannin, and derivatives with higher specificity and potency 12,13 . Moreover, the use of comparative transcriptomics (e.g., [14][15][16] ) and proteomics 17 approaches for elucidating the shikonin/alkannin pathway has uncovered several gene candidates and led to the identification of the geranylhydroquinone hydroxylase (GHQH; CYP76B74) 18 . Comparatively less attention has focused on the evolutionary origin of shikonin/alkannin pathway genes 16,19 and on the ecological significance of producing the compounds 3 .…”
Section: Introductionmentioning
confidence: 99%